A comparative study of the early stages of mercury, cadmium, lead, silver and copper electrodeposition on columnar and smooth platinum electrodes - Martins, María Elisa (1996)
The early stages of metal (M) electrodeposition (M = Cu, Ag, Pb, Cd and Hg) on columnar and smooth Pt substrates (S) were investigated in acid solutions applying potentiodynamic techniques. At moderate and high potential scanning rates M electrodeposition on columnar substrates yields M domains which are dominated either by M-S interactions (M-S domains) or M-M interactions (M-M domains) as deduced from anodic stripping data. The roughness of S, the rate of surface diffusion of M atoms and the exchange current density of the M/Mz+ electrode reaction have a remarkable influence on the growth mode of the M overlayer. Rearrangements involving M-S and M-M domains leading to equilibrium at the M overlayer were deduced from voltammetric data. The rate of these rearrangements depends mainly on the surface diffusion of M atoms. Correlations between the charge related to M-S domains and ∆Hs, the enthalpy of sublimation, and Tm, the melting temperature of M, were established. These parameters reflect the trend of M atoms to participate in surface diffusion processes.